Invasion by the weed Conyza canadensis alters soil nutrient supply and shifts microbiota structure. (April 2020) - Zhang, Hai-Yan; Goncalves, Priscila; Copeland, Elizabeth; Qi, Shan-Shan; Dai, Zhi-Cong; Li, Guan-Lin; Wang, Cong-Yan; Du, Dao-Lin; Thomas, Torsten
Abstract: Modifications in soil fertility and microbiota structure driven by invasive plants can initiate a self-promoting mechanism that facilitates their invasion process. This study aimed to resolve how the progression of invasion affects the chemical, biochemical and microbial properties of soil using Conyza canadensis, a widespread and noxious invasive farmland weed, as a model. Different stages of the invasion process were simulated by growing C. canadensis and a non-invasive crop, Lactuca sativa, at different relative densities. Increasing invasion levels (i.e. increasing invader relative densities) resulted in altered properties of the soil, with an overall increase in nutrient supply and enzymatic activities as invasion intensified. Threshold changes in available nitrogen, organic matter and catalase activity in the soil were identified at invasion levels of 69%, 50% and 47%, respectively. Increasing invasion levels also affected the structure of the soil microbiota, with substantial changes occurring in the relative abundance for a number of bacterial and fungal taxa, including some that are relevant to nutrient cycling. Such changes in soil abiotic and biotic composition driven by C. canadensis might lead to positive plant-soil feedbacks that could promote the establishment and spread of the invasive weed. Graphical abstract: Image 1 Highlights: Different invasion levels of Conyza canadensis were simulated in pot trials. Nutrients contents and enzyme activities increased with the higher invasion levels. Invasion thresholds were identified for soil nitrogen, organic matter and catalase. Invasion levels affected some microbes related to nutrient-cycling. Positive plant-soil feedback might be involved in the spread of weed C. canadensis.